A study of up to 12 years of follow-up of Friedreich ataxia utilising four measurement tools. Issue 6 (11th August 2014) - Tai, Geneieve; Corben, Louise A; Gurrin, Lyle; Yiu, Eppie M; Churchyard, Andrew; Fahey, Michael; Hoare, Brian; Downie, Sharon; Delatycki, Martin B
Abstract : Objective: To explore the progression of Friedreich ataxia by analysing the change in scores of four clinical measures (the Friedreich Ataxia Rating Scale (FARS), the International Cooperative Ataxia Rating Scale (ICARS), the Functional Independence Measure (FIM) and the Modified Barthel Index (MBI)) over a period of up to 12 years, to ascertain the effects of clinical variables on performance of these measures, and to determine the most sensitive rating scale for measuring disease progression. Methods: We measured the disease progression of up to 147 individuals against disease duration grouped into 5-year intervals. Additional subgroups were created to study the effects of the size of the smaller FXN intron 1 GAA repeat size (GAA1) and onset age on rating scale performance. Results: Both the FARS and ICARS demonstrated greater change in the first 20 years post disease onset than in the subsequent 20 years during which there was little change in the mean score. While the FIM and MBI continued to deteriorate beyond 20 years post disease onset, floor effects were noted. As measured by the FARS, individuals with a larger GAA1 repeat were found to progress more quickly in the first 20 years of disease. Conclusions: Individuals with larger GAA1 repeat sizes and earlier ages of disease onset were shown to deteriorate at a faster rate and were associated with greater FARS and ICARS scores and lower FIM and MBI scores, which are indicative of greater disease severity.